PELATIHAN KONTEN DIGITAL BERBASIS MEDIA SOSIAL UNTUK PEMASARAN HASIL PERTANIAN KELOMPOK WANITA TANI RCR SEJAHTERA - Neneng Rachmalia Feta; P Priyono; Elin Panca Saputra; F Fitria; Agus Trihandoyo; Ableir Benny Purba; Melsi Kristiani Tafonao; Novum Rizki Farros Sitorus; Sherina Dinda Cahya Mulyana Sugianto (LPPM Universitas Nusa Mandiri, 2026)
This community service activity was motivated by the suboptimal utilization of social media as a marketing tool for agricultural products by the Women Farmer Group (KWT) RCR Sejahtera in Bojonggede, Bogor. Although the group had established social media accounts, the published content lacked structure, consistent visual identity, and effective promotional strategies. The objective of this program was to enhance the digital content creation capacity of KWT members through social media–based marketing to expand market access for their agricultural products. The implementation method consisted of three stages: preparation, training, and monitoring and evaluation. The activity involved 22 participants and employed pre-test, post-test, and satisfaction questionnaires as evaluation instruments to measure program effectiveness. The results indicated a significant improvement in participants’ understanding, increasing from 54.54% in the “understanding” category during the pre-test to 90.91% in the post-test, representing a 36.37% increase. Furthermore, the overall satisfaction score reached an average of 4.18, categorized as “Satisfied.” These findings demonstrate that the social media–based digital content training was effective in improving participants’ digital literacy and promotional skills. The program contributes to strengthening the group’s digital capacity and has the potential to expand market reach and enhance the competitiveness of agricultural products in a sustainable manner.